Pengaruh Lama Pengeringan dan Struktur Biji terhadap Karakteristik Fisik dan Kimia Biji Pepaya (Carica papaya L.) - Syofianti, Erika Nanda; Priyanto, Gatot (Seminar Nasional Lahan Suboptimal, 2024)
Syofianti, E. N., & Priyanto, G. (2023). Effect of drying time and seed structure on physical and chemical characteristics of papaya (Carica papaya L.) Seeds. In: Herlinda S et al.(Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 262–271).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Papaya (Carica papaya L.) is a plant with abundant nutritional content in which all parts of the plant can be utilized, including seeds that are often considered waste because they have a layer of sarcotesta with potential antioxidant that is interesting to study, especially related to the influence of the drying process on seeds characteristics. The objectives of the research were to determine the effect of drying time and seed structure on the physical and chemical characteristics of papaya seeds. The research method used is a factorial completely randomized design with two treatment factors, A (drying time) consists of 5 levels, A1 (0 days), A2 (2 days), A3 (4 days), A4 (6 days), and A5 (8 days) under sunlight (from 10:00 AM to 2:00 PM), and factor B (seed structure) consists of 2 levels, B1 (with sarcotesta layer) and B2 (without sarcotesta layer). Observed parameters include chemical characteristics (antioxidant activity, total phenol, moisture content, ash content) and physical characteristics (specific grafity). The results showed that drying duration and seed structure significantly affected the reduction of antioxidant activity, total phenol, moisture content, and specific grafity, as well as the increase in ash content of papaya seeds. Based on the results of the analysis showed that, the average value of IC50 was 217,94 - 892,79 ppm, the total phenol was 0,75 - 2,52 mg GAE/g, the moisture content was 6,39 % - 82,19 %, ash content was 1,55 % - 8,75 %, and specific grafity was 0,59 - 1,08 g/mL.